Home economics concepts, values, and learning competencies for Filipino kindergarten children - Abutal, Dulce Monina Constancia P.; Chua, Consuelo T. (Quezon City University of the Philippines Diliman, 2025)
This study argues that Home Economics education should begin at the kindergarten level, a foundational period in child development, to help enable students to improve their quality of life in the long term as individuals and members of families and communities. It sought to identify and validate Home Economics concepts, values, and learning competencies for Filipino kindergarten children, and to test selected competencies. A total of 23 experts in Home Economics Education, Family Life and Child Development, and Teaching Early Grades responded to an online survey to get their consensus on developmentally appropriate Home Economics content for Filipino kindergarten children; which yielded concepts that include clothing, food, and home management; values such as cleanliness, orderliness, and responsibility; and competencies like eating nutritious foods and practicing proper hygiene habits. Learning activity plans on four randomly selected Home Economics competencies were designed for the pilot testing participated in by 77 kindergarten children, which showed what they know, what they want to know, and what was learned. It appears that some of the competencies are already being targeted in the national kindergarten curriculum under different learning areas, and suggestions were made on how to emphasize a Home Economics perspective in classroom instruction. The need to validate more content to cover all the child development areas and curricular themes was also underscored. Further research may be conducted to support the creation of a developmentally appropriate national kindergarten curriculum framework that recognizes Home Economics as an integral learning area.
In partial fulfillment for the Degree of Doctor of Philosophy in Home Economics
Dissertation
Keywords: Home economics -- Study and teaching (Early childhood) -- Philippines; Kindergarten -- Curricula; Early childhood education -- Philippines; Home economics